Association of Apolipoprotein L-1 polymorphisms with blood pressure in three multi-ethnic African studies. (2018) - , Shuchi Anand; , Safa Abdalla; Gathecha, Gladwell; Oladapo, Olulola O; Joseph, Kibachio; Montez-Rath, Maria E; Aslan, Marcella; Barry, Michele; Chertow, Glenn M; Rotimi, Charles; Friedman, David
No abstract available